Pengaruh Model Pembelajaran Teaching Factory (TEFA) dalam Meningkatkan Kompetensi Peserta Pelatihan Pengelasan - Decky Antony Kifta; Ambiyar Ambiyar; Fahmi Rizal (Jurnal Abdimas Adpi Sosial dan Humaniora, 2023)
The purpose of this research is to understand and obtain information regarding the competence of the students after experiencing learning method using Teaching Factory (TEFA) Learning Model. The research is performed at the welding vocational training center, ATS Training Center, located in Batam, Indonesia. Batam Island, located in vicinity with Singapore, is now considered as an industrial city where welding industry becomes one of promising professions. The training center was having more than 50 students and the class is divided into two groups (i.e., test group and control group). From the research it was obtained that the students with experiencing Teaching Factory learning model are more competent than the ones which are not using the learning model or those which are in controlled group. This research was using quasi experiment method with one-group pretest-posttest design. The researcher was using questionnaires and from the respondents’ surveys analysis, it is inferred that the level of competence of the TEFA students are with the score and N-Gain of 78.55% and 0.09 which are higher than controlled group.